Job satisfaction and turnover crisis in Malaysia’s hospitality industry - Suleiman Albattat, Ahmad Rasmi; Mat Som, Ahmad Puad (2013)
Turnover crisis reducing has been highlighted as a remarkable research theme in the hospitality industry. Regardless of the significant number of studies on employee turnover, it remains a vague issue and requires further research, It is well known that the service industry is highly dependent on the “human factor” which has become a major part of the hospitality product. The aim of this study is to give a clearer idea of enhancing employment factors to reduce the turnover crisis, Mobley`s model (1977) determined how job dissatisfaction can lead to job turnover. The results of this study will show that improving the work environment and increased wages, by analyzing the internal and external factors, could decrease the turnover crisis, An intention to stay within the hospitality organization amongst, unacceptable working conditions, poor training and low salaries could lead to higher employee turnover.